1987
DOI: 10.1159/000298806
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture before Delivery: Effect on Labor

Abstract: Acupuncture treatment in the final weeks of pregnancy has been claimed to shorten the duration of labor in primiparous women. In the present study, the length of the various phases of labor was calculated for 56 primiparous women who were repeatedly treated with manual acupuncture during the month prior to parturition. In vaginally delivering women, the average lengths of the latent and active phase and the second stage of labor were 4.1, 3.4 and 1.4 h, respectively. In a nontreated control group of 112 primip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 7 publications
0
13
2
Order By: Relevance
“…Our findings suggest that AP treatment has an effect on the cervix, inducing a more rapid maturing of the cervix. This is in contrast to the results of Lyrenäs et al [13] who found no beneficial effect on the maturation of the cervix. The comparison of our findings concerning the duration of the first stage of labor with previous reports is difficult because of the lack of an established definition of the first stage of labor [12,13].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our findings suggest that AP treatment has an effect on the cervix, inducing a more rapid maturing of the cervix. This is in contrast to the results of Lyrenäs et al [13] who found no beneficial effect on the maturation of the cervix. The comparison of our findings concerning the duration of the first stage of labor with previous reports is difficult because of the lack of an established definition of the first stage of labor [12,13].…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to the results of Lyrenäs et al [13] who found no beneficial effect on the maturation of the cervix. The comparison of our findings concerning the duration of the first stage of labor with previous reports is difficult because of the lack of an established definition of the first stage of labor [12,13]. There is no objective method available to ascertain when effective myometrial contractions start.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations